2012
DOI: 10.1097/prs.0b013e31825dc18b
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Adjustment of Toddler and Preschool-Aged Children with Single-Suture Craniosynostosis

Abstract: Background The purpose of this study was to confirm initial reports of elevated behavior problems in children with single-suture craniosynostosis (SSC), using multiple informants, longitudinal analyses and a control group. We hypothesized higher levels of maladjustment for children with SSC than comparison children, particularly at the older age and in selected areas of previously observed vulnerability: attention and social adjustment. Method A Child Behavior Checklist (CBCL) was completed when children wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
3
17
1
Order By: Relevance
“…Group differences on these tasks were negligible, though fewer children with SSC than controls were able to complete the most challenging tasks, possibly indicating problems with EF under more demanding conditions. We also found slightly greater attention problems in children with SSC versus controls at age 36 months based on parent, but not teacher reports (Kapp-Simon et al, 2012). …”
mentioning
confidence: 66%
“…Group differences on these tasks were negligible, though fewer children with SSC than controls were able to complete the most challenging tasks, possibly indicating problems with EF under more demanding conditions. We also found slightly greater attention problems in children with SSC versus controls at age 36 months based on parent, but not teacher reports (Kapp-Simon et al, 2012). …”
mentioning
confidence: 66%
“…Muenke syndrome is a molecular diagnosis based on a P250R mutation in FGFR3 and does not require craniosynostosis as a diagnostic criterion. Although previous research has examined similar constructs in craniosynostoses 11,14 , and case studies have collected data on behavior and development of individual patients with FGFR3 -related craniosynostosis 10,1213,1516,20 , these studies have had small numbers of participants. Evaluating 13 children with Muenke syndrome, Maliepaard et al found that parents of individuals with Muenke syndrome reported higher levels of behavioral and emotional problems compared with parents of children of other craniosynostosis syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…However, cranial vault volume (CVV) in patients with sagittal synostosis has been reported to be the same or higher than normal controls (Lee SS, et al, 2010, Heller JB, et al, 2008, Anderson PJ, et al, 2007, Netherway DJ, et al, 2005, Posnick JC, et al, 1995). Currently, it is unclear whether cognitive and functional deficits are due to primary brain abnormalities or altered cranial vault morphology (Kapp-Simon KA, et al, 2007; Kapp-Simon KA, et al 2012; Sgouros S, 2005, Sgouros S, et al, 1999). …”
Section: Introductionmentioning
confidence: 99%